AGE-RELATED CHANGES IN PEOPLE OVER 60: IMPLICATIONS FOR SECOND LANGUAGE LEARNING AND TEACHING. - Pace, Cinzia; Topini, Alessandra (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Longer life expectancy and easier ways of traveling have modified the over- 60’s way of life in rich countries. The concept of life-long learning, the desire for self-fulfillment, and the interest in cultures different from one’s own are the main reasons why people over 60 take up language courses abroad or in their own country. Our paper examines the over-60s in relation to their increasing demand for foreign language courses. The age-related physical and psychological changes of this group that could have an influence on the language learning process should be considered by the teacher, e.g. when deciding the language teaching techniques to be employed. Furthermore, knowledge of the over-60’s specific needs, abilities and potential could be applied to the design of a targeted foreign language syllabus. The aging process is different in each individual and some suggestions for language teaching might not be necessary for those who are not subject to the age-related changes mentioned; they can however make the teaching and learning process easier in language classes made up entirely of people over 60.